1988
DOI: 10.1038/jcbfm.1988.104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Piracetam on Cerebral Glucose Metabolism in Alzheimer's Disease as Measured by Positron Emission Tomography

Abstract: Summary:The effect of piracetam (a putative enhancer of cerebral metabolism) on regional CMRalu was studied by positron emission tomography of 2[18Fl-fluoro-2-deoxY-D-glucose in nine patients with Alzheimer's dis ease, and in seven cases with multiinfarct dementia or unclassified dementia. In Alzheimer's disease, i. v. ad ministration of piracetam, 6 g b.i.d. for 2 weeks, signifi cantly improved rCMRalu in most cortical areas, whereas no effect on CMRalu of the drug was observed in the mul tiinfarct dementia/u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…In most of these trials the emphasis was on examining whether the drug would increase cerebral glucose metabolism as a pharmacodynamic effect of treatment rather than on assessment of progression. Typically these were short trials of a few weeks or up to 3 mo active treatment duration with 18 F-FDG PET before and during treatment (20)(21)(22). Trials that were extended for at least 6 mo also showed evidence of disease progression by further reduction of glucose metabolism in association cortices (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…In most of these trials the emphasis was on examining whether the drug would increase cerebral glucose metabolism as a pharmacodynamic effect of treatment rather than on assessment of progression. Typically these were short trials of a few weeks or up to 3 mo active treatment duration with 18 F-FDG PET before and during treatment (20)(21)(22). Trials that were extended for at least 6 mo also showed evidence of disease progression by further reduction of glucose metabolism in association cortices (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of SND is based on clinical signs and evolution, particularly an absent or evanescent response to L-dopa 19, lo}. Computed tomography (CT) and magnetic resonance imaging (MRI) may reveal atrophy and iron deposits in the striaturn 111-131, but the specificity of these findings gional cerebral glucose metabolism and brain morphological features were studied in 7 patients with probable SND using positron emission tomography (PET) with "F-labeled 2-deoxy-2-fluoro-D-glucose (FDG) as the tracer and proton MRI.…”
mentioning
confidence: 99%
“…In these impaired synapses with limited function, PS might be most effective. The nonselective increase in rCMRGl similar to that described for the metabolic enhancer pira cetam [26] is distinctly different from the selective ac tion of a muscarinergic cholinagonist which, during a 6-week treatment period, prevented the deterioration of glucose metabolism in areas typically involved in AD, while CMRG1 in other areas further decreased during treatment [27], Despite the preliminary character of this study, our data showed a significant effect of PS on regional glucose metabolism in a small number of AD patients. These data may form the basis for a larger clinical trial with a longer duration of PS treatment in which various mea sures of cognitive performance, neuropsychological defi cits.…”
Section: Discussionmentioning
confidence: 49%